Perbedaan Informasi Citra Anatomi Lumbal Sequence T2 Fat Suppresion Antara Metode SPAIR dan Dixion - Indira Mega Wahyuningtiyas; Nursama Heru Apriantoro (FORUM ILMIAH KESEHATAN, 2020)
Methods Fat Supression used in the MRI examination Lumbal are SPAIR and Dixion. SPAIR is a powerful technique in suppressing fat which has low sensitivity to the inhomogeneity of RF pulses, while Dixion is a technique Fat Suppression based on chemical shift, the difference in the frequency of larmor between fat and water and in one acquisition. However, technique Dixion has a relatively long scan time because the separation of water and fat takes time during the image reconstruction process. SPAIR is used as a protocol for MRI examination Lumbal and is considered to be better at producing images. However, based on the study Dixion is more homogeneous in suppressing fat compared to SPAIR. The purpose of writing this paper as to determine differences in anatomical information MRI Lumbal T2 sequences Fat Suppression sagittal slices between SPAIR method and Dixion and to investigate methods of Fat Suppression better in MRI revealed of information image in Lumbal. This research was descriptive qualitative. The population and sample in this study were those who performed the MRI examination Lumbal, based on a literature review at the National Library of Medicine (PubMed) website and the American Journal of Roentgenology (AJR). The data collection method used was literature study or literature review, reviewing journals and scientific articles. Processing and data analysis in this study using descriptive analysis. The data obtained from the literature review are analyzed based on the the oretical basis that had been collected so that conclusions could be drawn on the research objectives. The results showed that there were differences in anatomical information on MRI Lumbal sagittal sequences T2 Fat Supression between SPAIR method and Dixion with ρ value